Optimization of Gigabit Passive Optical Network (GPON) Devices Replacement Interval - Muhammad Mahrus Syamsurrijal; Abdullah Shahab (Institut Teknologi Sepuluh Nopember, 2020)
Entering the industrial era that is increasingly advanced and growing, reliable internet connection becomes a very important foundation for every business. Internet connection failure or downtime will be the obstacle and causes much loss both for businessman and for internet provider company. This research aims to find a solution on how to minimize internet connection failure. One of the various methods that can be used to overcome the problem is called preventive maintenance. This research is chosen to determine how far the role of preventive maintenance in reducing the risk of connection failure due to device failure. Several tools that used in this research, such as statistical distribution to determine the pattern of device failure, and mathematical formula to calculate the estimated duration of the downtime occurs based on the time of preventive maintenance was applied. From that calculation, it can be concluded the optimal time to apply preventive maintenance to minimize downtime duration. The results reveal that a decreasing downtime value happens when preventive maintenance is applied at the optimal age of the device. EI8E - 8FE Electrical Interface Card kit was reduced by 8.01% with an optimal age of 21.82 days. GTGH - 16 Port GPON Line Card devices were reduced by 5.46% with an optimal age of 16.69 days. EMTPDP-DC Power Board devices are reduced by 0.1% with an optimal age of 53 days. The GPON MSVG - Control & Switching Card device is reduced by 4.38% with an optimal age of 32.28 days. MTPD - Power Supply equipment is reduced by 1.2% with an optimal age of 92.35 days. The ETC8B - 8E1 / T1 CES Card device was reduced by 0.84% with an optimal age of 41.23 days.